Alterations in the Gut Virome in Obesity and Type 2 Diabetes Mellitus - Yang, Keli; Niu, Junkun; Zuo, Tao; Sun, Yang; Xu, Zhilu; Tang, Whitney; Liu, Qin; Zhang, Jingwan; Ng, Enders K.W.; Wong, Simon K.H.; Yeoh, Yun Kit; Chan, Paul K.S.; et al. (Gastroenterology (New York, N.Y. 1943), 2021)
Obesity and type 2 diabetes mellitus (T2DM) are associated with changes in the gut bacterial composition, but little is known about the role of the viral community (virome) in disease development. This study aims to characterize the gut virome alterations in obese subjects with or without T2DM. There were 128 obese subjects (body mass index ≥28 kg/m2) and 101 lean controls (body mass index ≥18.5 and <23 kg/m2) recruited from 2 regions in China (Hong Kong and Kunming). Fecal virome and bacteriome were profiled by shotgun metagenomic sequencing. Gut virome, bacteriome, and viral-bacterial correlations were compared between obese subjects and lean controls. Obese subjects, especially those with T2DM (ObT2), had a decreased gut viral richness and diversity compared with lean controls in the Hong Kong cohort (P < .05), while no significant differences were observed in the Kunming cohort. Eleven viruses, including Escherichia phage, Geobacillus phage, and Lactobacillus phage were enriched in obese subjects (q < .1). Besides, 17 differentially abundant viruses were identified between ObT2 and lean controls (q < .1). Further ecologic analysis revealed that intensive transkingdom correlations between viruses and bacteria observed in lean controls were significantly decreased in ObT2 subjects (P < .001). Obesity is characterized by altered viral taxonomic composition and weakened viral-bacterial correlations compared with lean controls. Obesity accompanied with T2DM may aggravate the obesity-associated virus signatures, signifying that the gut virome may play an important role in the development of obesity and T2DM. Geographic factors also contributed to the variations of gut virome in obesity and T2DM. [Display omitted] Obese individuals have a dysbiotic gut virome, and type 2 diabetes mellitus further aggravates such dysbiosis.